Marketing channels, dynamics and economic incentives for onion production in Ethiopia: A case study from Oromiya Regional State, Ethiopia - Mentafa, H Birhanu-; Shiferaw, G Diriba-; Temesgen, M (Journal of Spices and Aromatic Crops, 2017)
This research was initiated to assess the market channels and develops value chain map and econometric model outputs for the onion in Ambo and Toke Kutaye districts of West Showa Zone, Oromiya Regional State, Ethiopia. Primary data were collected using interview guided questionnaires from 183 respondents’ of different actors in onion value chain and four focus group discussions of onion producers. Descriptive and inferential statistics; value chain mapping; marketing margin analysis; and econometrics analysis were used to analyze the data. About four marketing channels were identified in the study areas. The econometric result showed that education level of household, onion farming experience, number of oxen owned, land size used for onion farming, amount of fertilizer used, access to extension services and family size of house hold were variables those significantly influenced the marketable supply of onion at farmers level. Multiple linear regression model indicated that variables like age, farm experience, family size, selling price and improved inputs were significant in affecting onion marketable supply. Thus, to increase the onion productivity, market channel and performances of all actors to maximize the profits of all value chain actors, it is important to integrate all concerned bodies of the onion value chains along with the supporting sectors.